High-strength corrosion-resistant cloth for trampoline

By using PEVA matrix resin and adding zinc hydroxystannate, modified wollastonite, antibacterial agents and anti-aging agents in the trampoline fabric, multiple flame retardant and anti-aging protective layers are formed, which solves the aging problem of trampoline fabric during outdoor use and improves the corrosion resistance and service life of the material.

CN120682560APending Publication Date: 2025-09-23HANGZHOU TRANSASIA SPORTING GOODS MFR CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510827514.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-20
Publication Date
2025-09-23

AI Technical Summary

Technical Problem

Existing trampoline fabrics are easily aged due to prolonged exposure to sunlight when used outdoors, resulting in a shortened service life.

Method used

PEVA is used as the base resin, and zinc hydroxystannate, modified wollastonite, antibacterial agents, flame retardants and anti-aging agents are added to enhance the corrosion resistance and flame retardancy of the material by forming a dense carbon layer, physical barrier and chemical flame retardant system. The antibacterial and anti-aging agents are used to improve the antibacterial and anti-ultraviolet capabilities of the material.

Benefits of technology

The mechanical properties, antibacterial properties and anti-aging properties of the trampoline fabric are improved, the service life is extended, the risk of tearing and puncture is reduced, and the structural stability and flame retardant effect of the material are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a high-strength corrosion-resistant fabric for a trampoline, and relates to the technical field of trampoline fabrics, the high-strength corrosion-resistant fabric comprises 100 parts of matrix resin, 5-8 parts of a compatilizer, 30-50 parts of modified siliceous lime, 8-14 parts of an antibacterial agent, 8-12 parts of a flame retardant, 1.5-3 parts of an anti-aging agent, 0.5-1 part of a lubricant, and 0.3-0.5 part of an antioxidant. According to the high-strength corrosion-resistant cloth for the trampoline, zinc hydroxystannate is decomposed at a high temperature to generate metal oxides such as SnO2 and ZnO, a compact carbon layer is formed, heat transfer and combustible gas release are prevented, smoke in the combustion process is inhibited, meanwhile, ammonium polyphosphate is decomposed to generate phosphoric acid / polyphosphoric acid, PEVA dehydration and carbonization are promoted, and a carbon layer is formed to isolate oxygen; the charring capability of zinc hydroxystannate is combined with the acid source-gas source effect of ammonium polyphosphate to form multiple flame retardant effects of carbon layer enhancement, smoke suppression and combustion environment dilution; and the supporting effect of the carbon layer can enhance the structural stability of the material, reduce the tearing or puncturing risk and improve the mechanical property of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of trampoline fabrics, in particular to a high-strength, corrosion-resistant fabric for a trampoline. Background Art

[0002] Referring to the Chinese patent for an environmentally friendly sandwich fabric base film and its preparation method, and a sandwich fabric and its preparation method (Announcement No.: CN114213783A), the environmentally friendly sandwich fabric base film comprises the following components, calculated by weight: 100 parts PVC, 50-60 parts polyester polyol, 0.5-1 part UV absorber, 0.15-0.5 part antioxidant, 2.5-4 parts barium zinc stabilizer, and 0.3-2 parts processing aid. The polyester polyol has a molecular weight of 1000-1500. The sandwich fabric base film uses polyester polyol as a plasticizer, with a molecular weight of 1000-1500 to ensure solvent resistance and low precipitation, while also preventing processing difficulties and being non-carcinogenic. Antioxidants and barium zinc stabilizers are added to improve processing stability. However, most existing trampolines are used outdoors, which makes them prone to aging under long-term sunlight, thereby shortening their service life. To this end, the present invention proposes a high-strength corrosion-resistant fabric for trampolines to solve the above-mentioned problem. Summary of the Invention

[0003] (1) Technical problems solved

[0004] In view of the shortcomings of the existing technology, the present invention provides a high-strength corrosion-resistant fabric for a trampoline, which solves the problems mentioned in the above background technology.

[0005] (2) Technical solution

[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: A high-strength corrosion-resistant fabric for a trampoline, comprising 100 parts of a base resin, 5-8 parts of a compatibilizer, 30-50 parts of modified silica lime, 8-14 parts of an antibacterial agent, 8-12 parts of a flame retardant, 1.5-3 parts of an anti-aging agent, 0.5-1 part of a lubricant, and 0.3-0.5 parts of an antioxidant;

[0007] The base resin is PEVA, and the VA content is 15%-30%; the compatibilizer is maleic anhydride grafted polyethylene; the flame retardant is a mixture of zinc hydroxystannate and ammonium polyphosphate, and the mass ratio thereof is 2: (2.3-3.5);

[0008] The preparation method of the zinc hydroxystannate is as follows: 10-14 g of zinc chloride is poured into 25-30 mL of deionized water, and 0.8-1 g of hydrochloric acid is added dropwise, and 8-12 g of tin tetrachloride pentahydrate is added dropwise while stirring. After the addition is completed, 2.5-4.3 g of potassium hydroxide solution is added under high-speed stirring conditions, the temperature is raised to 50-55° C., and stirred for 30 minutes. After the reaction is completed, the mixture is aged at room temperature for 30 minutes, filtered and washed, and finally placed in a drying oven at 75-80° C. to obtain zinc hydroxystannate.

[0009] Preferably, the preparation method of the modified wollastonite is:

[0010] S1. Mix KH560 and ethanol to prepare solution A;

[0011] S2, mixing ethanol and stearic acid to prepare solution B;

[0012] S3. Pour the dried wollastonite into solution A, heat to 80-85°C, stir for 30 minutes, and then let stand to cool to room temperature;

[0013] S4, then pour solution B, heat to 80-85 ° C, stir for 20 minutes, and then ultrasonicate for 15 minutes;

[0014] S5. Perform rotary evaporation to evaporate the anhydrous ethanol, and then place the mixture in a drying oven at 65-70° C. for 20 hours to obtain modified silica lime.

[0015] Preferably, the weight proportions of the components in the preparation process of the modified wollastonite are: 25-32 parts of wollastonite, 0.4-0.8 parts of solution A, and 0.2-0.3 parts of solution B.

[0016] Preferably, in S1, the volume ratio of KH560 to ethanol is 1:(0.08-0.15), and in S2, the volume ratio of ethanol to stearic acid is 1:(0.05-0.07).

[0017] Preferably, the preparation method of the antibacterial agent is:

[0018] (1) Mix 10-15 g of zeolite molecular sieve with 100 mL of 0.5 mol / L ammonium chloride, and perform condensation reflux, suction filtration, and washing in sequence. Repeat this operation 5 times, and then dry at 50 °C;

[0019] (2) 5-7.2 g of the treated zeolite molecular sieve was mixed with 100 mL of 0.01 mol / L silver nitrate solution, and the mixture was subjected to condensation reflux, suction filtration, and washing in sequence. This operation was repeated three times, and then vacuum dried at 50°C.

[0020] (3) Place the product in a tubular furnace, heat it to 400°C at a heating rate of 5°C / min in an air atmosphere, keep it warm for 1 hour, and then cool it in the furnace to obtain the antibacterial agent.

[0021] Preferably, in (1) and (2), the condensation reflux temperature is 70-80°C and the time is 30 minutes.

[0022] Preferably, the preparation method of the anti-aging agent comprises dissolving 2-(2,4-dihydroxyphenyl)-2H-benzotriazole in anhydrous ethanol, adding a sodium carbonate solution under a nitrogen atmosphere, then slowly adding allyl glycidyl ether dropwise, and reacting at 75-80° C. for 7 hours; after the reaction solution is naturally cooled, the pH value of the solution system is adjusted to 6-7 with dilute hydrochloric acid, and then benzene is added for extraction, washing with water, and drying to obtain the anti-aging agent.

[0023] Preferably, the anti-aging agent comprises 2.27-2.58 parts by weight of 2-(2,4-dihydroxyphenyl)-2H-benzotriazole and 1.25-1.6 parts by weight of allyl glycidyl ether.

[0024] (3) Beneficial effects

[0025] The present invention provides a high-strength, corrosion-resistant fabric for a trampoline. Compared with the prior art, it has the following advantages:

[0026] (1) The trampoline uses high-strength corrosion-resistant fabric. The metal oxides such as SnO2 and ZnO are decomposed by zinc hydroxystannate at high temperature to form a dense carbon layer, which prevents heat transfer and the release of combustible gas and inhibits the generation of smoke during combustion. At the same time, ammonium polyphosphate decomposes to produce phosphoric acid / polyphosphoric acid, which promotes the dehydration and carbonization of PEVA to form a carbon layer to isolate oxygen. The carbon-forming ability of zinc hydroxystannate is combined with the acid source-gas source effect of ammonium polyphosphate to form a multiple flame retardant effect of "carbon layer enhancement + smoke suppression + dilution of combustion environment". The supporting effect of the carbon layer can enhance the structural stability of the material, reduce the risk of tearing or puncture, and improve the mechanical properties of the material.

[0027] (2) The high-strength corrosion-resistant fabric used in the trampoline is modified by the synergistic treatment of KH560 and stearic acid, which reduces the surface energy of wollastonite, enhances its lipophilicity, and significantly improves the interfacial bonding force, thereby improving the mechanical properties of the matrix. A hydrophobic coating is formed on the surface of the particles through physical adsorption or van der Waals force, producing a "steric hindrance effect" to prevent particle agglomeration. The agglomerates are further broken up by ultrasonic treatment, thereby improving the uniformity of the dispersion of wollastonite during PEVA melt blending, reducing the corrosion path caused by interface defects, and improving the corrosion resistance of the matrix material. The modified wollastonite particles can be embedded in the PEVA surface to form a "micro-convex" wear-resistant layer, reducing the direct wear between the fabric and the contact surface. At the same time, the inorganic skeleton of the modified wollastonite provides attachment sites for the flame retardant, delaying the diffusion and loss of the decomposition products of the flame retardant, and forming a "physical barrier + chemical flame retardant" synergistic system with the flame retardant.

[0028] (3) The trampoline is made of high-strength corrosion-resistant fabric. During the preparation of the antibacterial agent, the positive charge on the pore surface is increased by the introduction of ammonium ions, thereby enhancing the resistance to Ag through electrostatic action. + The adsorption capacity of Ag + Enter the zeolite pores and adsorb on the negatively charged sites (AlO4 - ), followed by heat treatment to promote some Ag + Reduced to silver nanoparticles (Ag 0 ), deposited in the pores or on the surface; ammonium ions decompose into NH3 and H2O and volatilize, further releasing pore space to form ionic Ag + With nano-Ag 0 The coexisting antimicrobial system combines long-lasting release with strong contact bactericidal ability.

[0029] (4) The trampoline uses high-strength corrosion-resistant fabric. By adding an anti-aging agent, after absorbing ultraviolet rays, the molecules can jump from the ground state to the excited state, and then release energy in the form of heat or fluorescence, avoiding the transfer of energy to the PEVA molecular chain, preventing it from breaking or generating free radicals, and the hydroxyl groups (-OH) in its molecules form hydrogen bonds with adjacent groups, enhancing the intramolecular stability and ensuring that it remains active after repeated absorption of ultraviolet rays; at the same time, through the modification of allyl glycidyl ether, cross-linking groups are introduced, so that the anti-aging agent is chemically bonded to the PEVA molecular chain, avoiding migration and loss, and prolonging the lasting effect; at the same time, the anti-aging agent is chemically bonded to the PEVA to form a stable "protective shell", reducing the shedding or leakage of the antibacterial agent due to aging of the matrix; at the same time, the porous structure of the zeolite molecular sieve can adsorb the decomposition products of the anti-aging agent, avoiding its chemical reaction with silver ions to reduce the antibacterial activity. DETAILED DESCRIPTION

[0030] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.

[0031] In the present application, the preparation method of 2-(2,4-dihydroxyphenyl)-2H-benzotriazole is as follows: under ice bath conditions, 8.28 g of o-nitroaniline and 0.2 mol of hydrochloric acid are poured into 100 mL of deionized water, mixed, and then 0.064 mol of sodium nitrate is poured into the mixture, reacted for 30 minutes, and then 2.52 g of urea is added. After stirring and reacting for 10 minutes, the mixture is filtered and then poured into a mixed solution of 10 g of m-diphenol, 200 mL of anhydrous ethanol and 180 mL of deionized water. After stirring and reacting for 3 hours, the mixture is filtered and recrystallized; 15.6 g of the recrystallized product is taken, and 200 mL of anhydrous ethanol and 200 mL of sodium hydroxide solution are added thereto, the temperature is raised to 70° C., thiourea dioxide is added, the reaction is continued for 50 minutes, and then hydrochloric acid is added under stirring to adjust the pH value of the solution system to 3. The mixture is then filtered and recrystallized to obtain 2-(2,4-dihydroxyphenyl)-2H-benzotriazole.

[0032] The lubricant is calcium stearate; the antioxidant is antioxidant 1010.

[0033] Example 1

[0034] (1) Preparation of zinc hydroxystannate: Pour 10 g of zinc chloride into 25 mL of deionized water, and add 0.8 g of hydrochloric acid dropwise. While stirring, add 8 g of tin tetrachloride pentahydrate dropwise. After the addition is completed, add 2.5 g of potassium hydroxide solution under high-speed stirring, heat to 50 ° C, stir for 30 minutes, and after the reaction is completed, age at room temperature for 30 minutes, then filter and wash, and finally dry in a drying oven at 75 ° C to obtain zinc hydroxystannate;

[0035] (2) Preparation of modified wollastonite: KH560 and ethanol were mixed in a volume ratio of 1:0.08 to prepare solution A; ethanol and stearic acid were mixed in a volume ratio of 1:0.05 to prepare solution B; the dried wollastonite was poured into solution A, heated to 80°C, stirred for 30 minutes, and then allowed to cool to room temperature; then poured into solution B, heated to 8°C, stirred for 20 minutes, and then ultrasonically treated for 15 minutes; after rotary evaporation, the anhydrous ethanol was evaporated, and the solution was dried in a drying oven at 65°C for 20 hours to obtain modified wollastonite;

[0036] (3) Preparation of antibacterial agent: 10 g of zeolite molecular sieve was mixed with 100 mL of 0.5 mol / L ammonium chloride, and filtered and washed after condensation and reflux at 70 ° C for 30 min, and the operation was repeated 5 times, and then dried at 50 ° C; 5 g of the treated zeolite molecular sieve was mixed with 100 mL of 0.01 mol / L silver nitrate solution, and filtered, washed, filtered, washed, and the operation was repeated 3 times, and then vacuum dried at 50 ° C; placed in a tube furnace, heated to 400 ° C at a heating rate of 5 ° C / min under air atmosphere, kept warm for 1 hour, and then cooled with the furnace to obtain the antibacterial agent;

[0037] (4) Preparation of anti-aging agent: 2.27 g of 2-(2,4-dihydroxyphenyl)-2H-benzotriazole was dissolved in 25 mL of anhydrous ethanol, and 10 mL of sodium carbonate solution was added under nitrogen atmosphere. Then 1.25 g of allyl glycidyl ether was slowly added dropwise and reacted at 75 °C for 7 h. After the reaction solution was cooled naturally, the pH value of the solution system was adjusted to 6 with dilute hydrochloric acid, and then benzene was added for extraction, washing with water, and drying to obtain an anti-aging agent.

[0038] (5) Pour 100 g of PEVA with a VA content of 15% into a high-speed mixer at 1200 rpm, heat it to 80 °C, add 8 g of antibacterial agent, 1.5 g of anti-aging agent and 0.3 g of antioxidant, continue to heat it to 100 °C, add 30 g of modified silica lime in batches (10 g each time), and finally add 1.5 g of a mixture of zinc hydroxystannate and ammonium polyphosphate with a mass ratio of 2:2.3 and 0.5 g of lubricant. After mixing for 5 minutes, twin-screw extrusion (130-150-160-170-175-170 °C) and then extension molding.

[0039] Example 2

[0040] (1) Preparation of zinc hydroxystannate: Pour 12 g of zinc chloride into 28 mL of deionized water, and add 0.9 g of hydrochloric acid dropwise. While stirring, add 10 g of tin tetrachloride pentahydrate dropwise. After the addition is complete, add 3.5 g of potassium hydroxide solution under high-speed stirring, heat to 52 ° C, stir for 30 min, and after the reaction is completed, age at room temperature for 30 min, then filter and wash, and finally dry in a drying oven at 78 ° C to obtain zinc hydroxystannate;

[0041] (2) Preparation of modified wollastonite: KH560 and ethanol were mixed in a volume ratio of 1:0.1 to prepare solution A; ethanol and stearic acid were mixed in a volume ratio of 1:0.06 to prepare solution B; the dried wollastonite was poured into solution A, heated to 82°C, stirred for 30 minutes, and then allowed to cool to room temperature; then poured into solution B, heated to 83°C, stirred for 20 minutes, and then ultrasonically treated for 15 minutes; after rotary evaporation, the anhydrous ethanol was evaporated and the solution was dried in a drying oven at 8°C for 20 hours to obtain modified wollastonite;

[0042] (3) Preparation of antibacterial agent: 12 g of zeolite molecular sieve was mixed with 100 mL of 0.5 mol / L ammonium chloride, and filtered and washed after condensation and reflux at 75 °C for 30 min, and the operation was repeated 5 times, and then dried at 50 °C; 6.1 g of the treated zeolite molecular sieve was mixed with 100 mL of 0.01 mol / L silver nitrate solution, and filtered, washed, filtered, washed, and the operation was repeated 3 times, and then vacuum dried at 50 °C; placed in a tube furnace, heated to 400 °C at a heating rate of 5 °C / min under air atmosphere, kept warm for 1 h, and then cooled with the furnace to obtain the antibacterial agent;

[0043] (4) Preparation of anti-aging agent: 2.42 g of 2-(2,4-dihydroxyphenyl)-2H-benzotriazole was dissolved in 25 mL of anhydrous ethanol, and 10 mL of sodium carbonate solution was added under nitrogen atmosphere. Then 1.4 g of allyl glycidyl ether was slowly added dropwise and reacted at 78 °C for 7 h. After the reaction solution was cooled naturally, the pH value of the solution system was adjusted to 6.5 with dilute hydrochloric acid, and then benzene was added for extraction, washing with water, and drying to obtain an anti-aging agent.

[0044] (5) Pour 100 g of PEVA with a VA content of 20% into a high-speed mixer at 1200 rpm, heat it to 80 °C, add 11 g of antibacterial agent, 2.2 g of anti-aging agent and 0.4 g of antioxidant, continue to heat it to 100 °C, add 40 g of modified silica lime in batches (10 g each time), and finally add 2.2 g of a mixture of zinc hydroxystannate and ammonium polyphosphate with a mass ratio of 2:3 and 0.7 g of lubricant. After mixing for 5 minutes, twin-screw extrusion (130-150-160-170-175-170 °C) and then extension molding.

[0045] Example 3

[0046] (1) Preparation of zinc hydroxystannate: Pour 14 g of zinc chloride into 30 mL of deionized water, and add 1 g of hydrochloric acid dropwise. While stirring, add 12 g of tin tetrachloride pentahydrate dropwise. After the addition is complete, add 4.3 g of potassium hydroxide solution under high-speed stirring, heat to 55 ° C, stir for 30 minutes, and after the reaction is completed, age at room temperature for 30 minutes, then filter and wash, and finally dry in a drying oven at 80 ° C to obtain zinc hydroxystannate;

[0047] (2) Preparation of modified wollastonite: KH560 and ethanol were mixed in a volume ratio of 1:0.15 to prepare solution A; ethanol and stearic acid were mixed in a volume ratio of 1:0.07 to prepare solution B; the dried wollastonite was poured into solution A, heated to 85°C, stirred for 30 minutes, and then allowed to cool to room temperature; then poured into solution B, heated to 85°C, stirred for 20 minutes, and then ultrasonically treated for 15 minutes; after rotary evaporation, the anhydrous ethanol was evaporated and the solution was dried in a drying oven at 70°C for 20 hours to obtain modified wollastonite;

[0048] (3) Preparation of antibacterial agent: 15 g of zeolite molecular sieve was mixed with 100 mL of 0.5 mol / L ammonium chloride, and filtered and washed after condensation and reflux at 80 ° C for 30 min, and the operation was repeated 5 times, and then dried at 50 ° C; 7.2 g of the treated zeolite molecular sieve was mixed with 100 mL of 0.01 mol / L silver nitrate solution, and filtered, washed, filtered, washed, and the operation was repeated 3 times, and then vacuum dried at 50 ° C; placed in a tube furnace, heated to 400 ° C at a heating rate of 5 ° C / min under air atmosphere, kept warm for 1 hour, and then cooled with the furnace to obtain the antibacterial agent;

[0049] (4) Preparation of anti-aging agent: 2.58 g of 2-(2,4-dihydroxyphenyl)-2H-benzotriazole was dissolved in 25 mL of anhydrous ethanol, and 10 mL of sodium carbonate solution was added under nitrogen atmosphere. Then 1.6 g of allyl glycidyl ether was slowly added dropwise and reacted at 80 °C for 7 h. After the reaction solution was cooled naturally, the pH value of the solution system was adjusted to 7 with dilute hydrochloric acid, and then benzene was added for extraction, washing with water, and drying to obtain an anti-aging agent.

[0050] (5) Pour 100 g of PEVA with a VA content of 30% into a high-speed mixer at 1200 rpm, heat it to 80 °C, add 14 g of antibacterial agent, 3 g of anti-aging agent and 0.5 g of antioxidant, continue to heat it to 100 °C, add 50 g of modified silica lime in batches (10 g each time), and finally add 4 g of a mixture of zinc hydroxystannate and ammonium polyphosphate with a mass ratio of 2:3.5 and 1 g of lubricant. After mixing for 5 minutes, twin-screw extrusion (130-150-160-170-175-170 °C) and then extension molding.

[0051] Comparative Example 1

[0052] Compared with Example 1, the difference is that the modified silica lime is replaced by silica lime; the rest remains unchanged.

[0053] Comparative Example 2

[0054] Compared with Example 1, the difference is that the flame retardant is replaced by ammonium polyphosphate; the rest remains unchanged.

[0055] Comparative Example 3

[0056] Compared with Example 1, the difference is that no anti-aging agent is added; the rest remains unchanged.

[0057] Comparative Example 4

[0058] Compared with Example 1, the difference is that the antibacterial agent is replaced by zeolite molecular sieve; the rest remains unchanged.

[0059] Accelerated aging test: Use fluorescent ultraviolet lamp to simulate sunlight in an accelerated aging tester at a temperature of 60°C and 0.89W / m 2 / nm UV radiation was used to conduct UV aging experiments on polyester fabrics before and after modification. The samples were clamped in the instrument tray and taken out after being exposed to UV radiation for a specific time (100h). Then, the breaking strength (warp direction) of the samples was tested in accordance with GB / T 3923.1. The results are shown in Table 1.

[0060] Antibacterial performance test: The test was conducted in accordance with GB / T 20944.2-2007, and the antibacterial rate was calculated. The results are shown in Table 1.

[0061] Table 1

[0062]

[0063] Abrasion resistance test: The test was conducted according to GB / T 30314-2021, with 50 cycles and the mass loss rate calculated. The results are shown in Table 2.

[0064] Corrosion resistance test: The test was conducted in accordance with GB / T 10125-2021 (immersed in dilute hydrochloric acid and sodium hydroxide solutions for 24 hours, respectively), and the mass loss rate was calculated. The results are shown in Table 2.

[0065] Flame retardant performance test: The limiting oxygen index (LOI) of the test sample was tested in accordance with GB / T 5454-1997; the results are shown in Table 2.

[0066] Table 2

[0067]

[0068] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.

[0069] It should be noted that, in this document, relational terms such as first and second, etc., are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the terms "comprises," "comprising," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a list of elements includes not only those elements but also other elements not explicitly listed, or elements inherent to such process, method, article, or apparatus.

[0070] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.

Claims

1. A high-strength, corrosion-resistant fabric for a trampoline, characterized by: The invention comprises 100 parts of base resin, 5-8 parts of compatibilizer, 30-50 parts of modified silica lime, 8-14 parts of antibacterial agent, 8-12 parts of flame retardant, 1.5-3 parts of anti-aging agent, 0.5-1 parts of lubricant and 0.3-0.5 parts of antioxidant; The base resin is PEVA, and the VA content is 15%-30%; the compatibilizer is maleic anhydride grafted polyethylene; the flame retardant is a mixture of zinc hydroxystannate and ammonium polyphosphate, and the mass ratio thereof is 2: (2.3-3.5); The preparation method of the zinc hydroxystannate is as follows: 10-14 g of zinc chloride is poured into 25-30 mL of deionized water, and 0.8-1 g of hydrochloric acid is added dropwise, and 8-12 g of tin tetrachloride pentahydrate is added dropwise while stirring. After the addition is completed, 2.5-4.3 g of potassium hydroxide solution is added under high-speed stirring conditions, the temperature is raised to 50-55° C., and stirred for 30 minutes. After the reaction is completed, the mixture is aged at room temperature for 30 minutes, filtered and washed, and finally placed in a drying oven at 75-80° C. to obtain zinc hydroxystannate.

2. The high-strength, corrosion-resistant fabric for a trampoline according to claim 1, characterized in that: The preparation method of the modified wollastonite is: S1. Mix KH560 and ethanol to prepare solution A; S2, mixing ethanol and stearic acid to prepare solution B; S3. Pour the dried wollastonite into solution A, heat to 80-85°C, stir for 30 minutes, and then let it stand and cool to room temperature; S4, then pour solution B, heat to 80-85 ° C, stir for 20 minutes, and then ultrasonicate for 15 minutes; S5. Perform rotary evaporation to evaporate the anhydrous ethanol, and then place the mixture in a drying oven at 65-70° C. and dry for 20 hours to obtain modified silica lime.

3. The high-strength, corrosion-resistant fabric for a trampoline according to claim 2, characterized in that: The weight proportions of the components in the preparation process of the modified wollastonite are: 25-32 parts of wollastonite, 0.4-0.8 parts of solution A, and 0.2-0.3 parts of solution B.

4. The high-strength, corrosion-resistant fabric for a trampoline according to claim 2, characterized in that: In the S1, the volume ratio of KH560 to ethanol is 1:(0.08-0.15), and in the S2, the volume ratio of ethanol to stearic acid is 1:(0.05-0.07).

5. The high-strength, corrosion-resistant fabric for a trampoline according to claim 1, characterized in that: The preparation method of the antibacterial agent is: (1) Mix 10-15 g of zeolite molecular sieve with 100 mL of 0.5 mol / L ammonium chloride, and perform condensation reflux, suction filtration, and washing in sequence. Repeat this operation 5 times, and then dry at 50 °C; (2) 5-7.2 g of the treated zeolite molecular sieve was mixed with 100 mL of 0.01 mol / L silver nitrate solution, and the mixture was subjected to condensation reflux, suction filtration, and washing in sequence. This operation was repeated three times, and then vacuum dried at 50°C. (3) Place the product in a tubular furnace, heat it to 400°C at a heating rate of 5°C / min in an air atmosphere, keep it warm for 1 hour, and then cool it in the furnace to obtain the antibacterial agent.

6. The high-strength, corrosion-resistant fabric for a trampoline according to claim 5, characterized in that: In (1) and (2), the condensation reflux temperature is 70-80°C and the time is 30 minutes.

7. The high-strength, corrosion-resistant fabric for a trampoline according to claim 1, characterized in that: The preparation method of the anti-aging agent comprises the following steps: dissolving 2-(2,4-dihydroxyphenyl)-2H-benzotriazole in anhydrous ethanol, adding a sodium carbonate solution under a nitrogen atmosphere, then slowly adding allyl glycidyl ether dropwise, and reacting at 75-80° C. for 7 hours; after the reaction solution is naturally cooled, adjusting the pH value of the solution system to 6-7 with dilute hydrochloric acid, then extracting with benzene, washing with water, and drying to obtain the anti-aging agent.

8. The high-strength, corrosion-resistant fabric for a trampoline according to claim 7, characterized in that: The anti-aging agent comprises: 2.27-2.58 parts by weight of 2-(2,4-dihydroxyphenyl)-2H-benzotriazole and 1.25-1.6 parts by weight of allyl glycidyl ether.

Citation Information

Patent Citations

  • Environment-friendly netted sandwich cloth base film and preparation method thereof, netted sandwich cloth and preparation method thereof

    CN114213783A

  • Anti-static composite material and preparation method thereof

    CN107746497A

  • Modifier, modified wollastonite modified by modifier, and preparation method and application of modified wollastonite

    CN112646395A

  • Zinc hydroxystannate and ammonium polyphosphate compound and preparation method thereof

    CN113956536A

  • High-strength PEVA netted cloth for trampoline

    CN118931030A